The association between pubertal timing and quality of life among children and adolescents: a cross-sectional study in Chongqing, China - Yang Pu; Yinshuang Tang; Qiuling Shi; Hong Wang (Komiyama Printing Co. Ltd, 2022)
Background: To determine the relationship between pubertal timing and quality of life (QOL) in children and adolescents and to provide a basis for QOL intervention in pubertal children in the future to promote good adaptation and healthy physical and mental development of children. Methods: The survey was conducted in one county using a stratified cluster sampling method. The five physiological change items of the Puberty Development Scale (PDS) were used to assess the timing of puberty in students. Compared to students of the same age and the same sex, students who scored higher than the mean + standard deviation (SD) of individual developmental scores were defined as an early pubertal timing group. A 39-item QOL Scale for Children in Puberty was used to assess the QOL of the respondents. Multiple linear regression models were fitted separately for boys and girls. Results: Of the 7223 students, 3754 (51.97%) were boys and 3469 (48.03%) were girls. The prevalence of early pubertal periods was 16.07%. The total QOL score in the early pubertal timing group (137.16 ± 18.67) was significantly lower than in the normal (on time) group (142.02 ± 17.98) and the late group (142.76 ± 18.35) (F = 37.311, P < 0.001). A multiple linear regression model showed that early pubertal timing was a risk factor for QOL (P < 0.0014), compared with normal and late pubertal timing. Conclusions: The early pubertal timing was associated with poorer QOL in children and adolescents. More attention should be paid to children with early pubertal timing in intervening children's QOL during pubertal development. Future longitudinal studies are needed to confirm the association between pubertal timing and QOL.